Effect of Inter-Professional Labor Management Guidelines on Adverse Outcomes in an Academic Labor and Delivery Unit [21D]. (May 2016) - Gecsi, Kimberly S.; Sammarco, Anne; Tapaskar, Natalie; Hackney, David
Abstract : INTRODUCTION: Much of the decision to pursue Cesarean delivery (CD) rests upon physician judgment. It has been suggested that institutions adopt policies regarding criteria for Cesarean delivery. This study assesses the impact of inter-professional departmental evidence-based guidelines that define active phase, arrest of labor, and failed induction of labor on provider management, documentation of labor progress, and adverse outcomes. METHODS: A retrospective cohort analysis of unscheduled CDs was performed from 2011 to 2013 at MacDonald Women's Hospital before and after guideline implementation. Compliance to guidelines was defined as documentation of active phase and CD for arrests within the recommended time frame. Outcomes were evaluated with Fisher exact and Mann-Whitney U tests. The adjusted monthly odds of guideline compliance were compared to the monthly severity index (SI) via meta-regression. RESULTS: A total of 465 women were included. Guideline implementation improved active phase documentation (45.3% from 22.9%, P =.002). No differences were identified in rates of chorioamnionitis, indication for CD, duration of second-stage or number of hours without cervical change prior to CD for arrest, though there was a trend ( P =.056) towards decreased unscheduled CDs. There was also a trend ( P =.057) towards decreasing SI in months that also demonstrated increased odds of guideline compliance. CONCLUSION: By introducing evidence-based inter-professional labor guidelines, we report increased documentation of labor progress and a trend towards decreased total adverse outcomes when labor guidelines were followed. Further research with larger cohorts is required to assess guideline impact on CD rates.